Effect of exponentially graded material on photonic and omni-directional band gaps in 1-D photonic crystals - Singh B.K.; Pandey P.C. (My University, 2025)
Photonic and Omni-directional band gaps have been obtained for one-dimensional (1-D) photonic crystal consists of exponential graded index material and constant refractive index material in range 150-750 THz of electromagnetic radiation. Transfer matrix method has been used for calculation of reflectance. The number of photonic band gaps and their bandwidths has been tuned by changing relative parameters, thickness of exponentially graded material and angle of incidence. This work will be useful in design of filters, optical sensors, reflectors etc., and provide more design freedom for alternative photonic devices. © Springer International Publishing Switzerland 2016.